2009
DOI: 10.1016/j.juro.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Defined Populations of Bone Marrow Derived Mesenchymal Stem and Endothelial Progenitor Cells for Bladder Regeneration

Abstract: Data demonstrate that mesenchymal stem cells and smooth muscle cells express the same contractile proteins and can function similarly in vitro. Endothelial progenitor cells also have the ability to form vasculature in an in vivo chorioallantoic membrane model. These findings provide evidence that mesenchymal stem cells and endothelial progenitor cells have characteristics that may be applicable for bladder tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…The characterization of a battery of contractile proteins shows that MSCs have a contractile protein profile similar to bSMCs [8]. Further data presented in this study demonstrate both cell types can also respond to agonist stimulation with statistically indistinguishable contractile responses in vitro.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The characterization of a battery of contractile proteins shows that MSCs have a contractile protein profile similar to bSMCs [8]. Further data presented in this study demonstrate both cell types can also respond to agonist stimulation with statistically indistinguishable contractile responses in vitro.…”
Section: Introductionmentioning
confidence: 55%
“…Experimental data has demonstrated the utility of bone marrow (BM) cells in a bladder regenerative setting with data suggesting the phenotypic and physiological similarities between mesenchymal stem cells (MSCs) and bSMCs [7][8][9]. The characterization of a battery of contractile proteins shows that MSCs have a contractile protein profile similar to bSMCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…(Quirici, 2001) Sharma et al describe the in vivo potential of this cell population as it was seeded within a chicken chorioallantoic membrane model. (Sharma, 2009) Post experimentation analyses of this work clearly demonstrate the angiogenic potential of bone marrow derived CD34 + /CD133 + cells as human specific vasculature was formed utilizing this model. Other derivatives of this cell population including CD34 + /CD133 + /VEGFR2 + , CD34 + /CD133 + /VEGFR3 + , CD34 + /VEGFR2 + , and CD133 + /VEGFR2 + cells maintain similar properties.…”
Section: Bone Marrow Derived Endothelial Progenitor Cellsmentioning
confidence: 67%
“…(Sharma, 2009) The mesenchymal stem cells utilized throughout this study as well as subsequent studies were an epitope defined population of highly purified mesenchymal stem cells. This study further demonstrated that both populations of cells can respond to agonist stimulation with statistically indistinguishable contractile responses in vitro while possessing similar contractile machinery.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Recently, BMSC were evaluated as an alternative cell type for use in replacement of bladder SMC when native bladder muscle tissue is unavailable. The potential of BMSC to differentiate into cells with bladder SMC characteristics was assessed in vitro 72 and in different animal models [73][74][75][76][77][78] . Kanematsu et al 75 showed that in vitro, both supernatants from cultured rat bladder cells (conditioned media) or media containing TGFand VEGF induced bone marrow cells to adopt a SMC phenotype.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%